Epidemiology, Prevention and Control of Foodborne Microbial Pathogens - Rossi, Gabriel Augusto Marques; Pereira, Juliano Gonçalves [UNESP]; Nitschke, Marcia (MDPI, 2025)
Foodborne diseases are caused by the consumption of food or water contaminated with bacteria and their toxins, viruses, parasites, or chemical substances [...].